The Concept of Active Voice Reduction using Multipole Secondary Source: Case Study of C-150 Aircraft - Muhammad Kusni (The Indonesian Institute of Science and Technology Research, 2022)
In order to protect residents living around the airport from aircraft noise disturbance, regulations have been set for the maximum permissible noise level limit. One of the international regulations that regulate the limits of aircraft exterior noise levels is the Federal Aviation Regulation (FAR) part 36 of the United States Regulatory Agency, or the Civil Aviation Safety Regulation (CASR) part 36 of the national regulatory agency. In addition, for military purposes, observer planes are also needed with the lowest possible sound level such that they will not attract the enemy's attention. This paper contains the concept of active exterior sound control/elimination with an unconventional secondary source method (anti-noise), using the multipole secondary source method. Multipole secondary sources are developed based on Taylor series expansion to obtain higher order secondary sources, such as dipoles, quadrupoles, octopoles, and so on, which are used for noise canceling. A significant noise reduction can be obtained by using a high-order secondary source and by optimizing the power of the secondary source. Numerical simulation of noise reduction in the free field was carried out by this method. The simulation results show that noise reduction reaches 50 dB at 200 Hz. The method, which is still a concept, was then used to simulate noise reduction on a Cessna-150 aircraft.